THE PARLIAMENTARY SCRUTINY OF THE EUROPEAN UNION AFFAIRS IN LITHUANIA: THE FACTOR OF DIVERGENCE OF PARTIES’ PREFERENCES WITHIN A COALITION - ZIMINA, ŽANA (Politologija, 2012)
In the 1970s, the process of the European integration induced discussions about the deficit of democracy in the European Union (EU). The decreased power of national parliaments and the increased autonomy of the executive sphere are named as the aspects this problem. As this problem has been realised, the importance of the parliamentary scrutiny of the EU affairs increased significantly. The main question raised in this article is whether the level of preference divergence within the coalition determines the parliamentary scrutiny intensity of the EU affairs. The Lithuanian case is analysed. In the article, the levels of preference divergence of two political coalitions and the intensity of the parliamentary scrutiny of the EU affairs implemented in the period of their governance (06.07.2006–17.11.2008 and 18.11.2008–30.04.2012) are compared. The preferences of political parties are identified by using an expert survey. The intensity of parliamentary scrutiny is analysed with reference to the information provided in the protocols of the European Affairs Committee’s meetings.